Effect of relative humidity and light exposure on fluorescence compound dynamics, soluble solid and acidity of Japanese Citrus Iyokan during postharvest treatment - Muharfiza Muharfiza; Dimas Firmanda Al-Riza; Nie Sen; Yasushi Kohno; Tetsuhito Suzuki; Makoto Kuramoto; Yuichi Ogawa; Naoshi Kondo (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
The Miyauchi iyokan (iyokan) citrus fruit is typically harvested in late December to prevent damage from the winter weather. At the time of harvest, the ratio of Soluble Solids (SS) to acid content is generally low, commonly used to assess the quality of the juice. Therefore, the goal during postharvest treatment is to decrease the acid content and improve the SS levels. The quality of citrus can be influenced by environmental factors such as relative humidity (RH) and exposure to light, so it is important to monitor their effects. Hence, this study aims to observe the changes in internal quality indicators, such as the SS/acid ratio and fluorescence compounds, under different RH and light conditions to understand how the citrus characteristics are affected. The postharvest treatment involved storing the citrus fruit at temperatures between 5-10°C for two months under various conditions i.e., in the dark and exposed to light, with high RH (80-90%) and low RH (40-50%). The SS/acid ratio did not show significant changes during the two months of storage under any treatments. However, the high RH condition resulted in a slightly higher SS/acid ratio. Similarly, the Tryptophan-like compound did not exhibit any significant response to the different treatments. However, the intensity of fluorescence from polymethoxylated flavones (PMFs) was higher in the dark treatment compared to the light treatment. PMFs play various roles in signaling and defense mechanisms in plants. Additionally, there was a notable increase in PMFs after thirty days of storage, indicating a response to light-induced stress.